2016
DOI: 10.5194/amt-9-9-2016
|View full text |Cite
|
Sign up to set email alerts
|

The microwave properties of simulated melting precipitation particles: sensitivity to initial melting

Abstract: Abstract.A simplified approach is presented for assessing the microwave response to the initial melting of realistically shaped ice particles. This paper is divided into two parts: (1) a description of the Single Particle Melting Model (SPMM), a heuristic melting simulation for ice-phase precipitation particles of any shape or size (SPMM is applied to two simulated aggregate snow particles, simulating melting up to 0.15 melt fraction by mass), and (2) the computation of the singleparticle microwave scattering … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 21 publications
(18 reference statements)
0
15
0
Order By: Relevance
“…Several studies (e.g., [40][41][42][43]48]) indicated that the presence of supercooled droplets on the top of the snow clouds could strongly affect TBs from high frequency channels. Specifically, supercooled droplets tend to partially mask scattering by snow crystals, which complicates the detection of snow using passive microwave radiometers.…”
Section: Complementary Datasetmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies (e.g., [40][41][42][43]48]) indicated that the presence of supercooled droplets on the top of the snow clouds could strongly affect TBs from high frequency channels. Specifically, supercooled droplets tend to partially mask scattering by snow crystals, which complicates the detection of snow using passive microwave radiometers.…”
Section: Complementary Datasetmentioning
confidence: 99%
“…The snow microphysics is also very complex, and a snow cloud is often composed of a gamut of snow particles with a variety of densities, shapes, particle size distributions and radiative properties [34][35][36][37][38][39]. In addition, supercooled droplets and melting snow frequently occur and can strongly affect the observed signal [16,[40][41][42]. Finally, while the active sensors, such as CPR, provide vertical information on snow clouds, passive instruments only offer integrated information that combines the radiative signal of every cloud layer.…”
Section: Introductionmentioning
confidence: 99%
“…Microphysical properties such as density are often arbitrarily assumed to change as a linear function of the melted fraction, and no direct connection is modeled between the heat balance and the distribution of ice, liquid water, and air during the transition. More recently, Botta et al (2010) and Johnson et al (2016), motivated by the need to produce shape models for microwave scattering simulations, have described more detailed three-dimensional (3-D) models that heuristically reproduce melting phenomena observed in real snowflakes. However, to our knowledge, a detailed model based on direct numerical simulation of physical phenomena has not been previously published for simulating the melting process at a single-particle level.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figures 4a and 4b, the observed results both for Ka-and W-bands agree reasonably well with Matrosov's relations, at least in cases where the rain rate is less than 3 mm/hr (Z < 30 dBZ). Such good agreement is noteworthy, given the recent discussion of the applicability of the Effective-Medium Approximation for modeling scattering properties of snowflakes and melting ice particles (Johnson et al, 2016). It could possibly be explained by the fact that the forward scattering computations do not necessarily need complex particle models, as shown by scattering computations of snowflakes (e.g.…”
Section: Parametrizations Of Melting Layer Attenuationmentioning
confidence: 56%
“…At millimeter wavelengths, melting layer models are capable of reproducing radar signatures, such as the distinct dark band at the upper part of the melting layer (Kollias & Albrecht, 2005). However, due to the lack of knowledge on thermodynamical (Leinonen & von Lerber, 2018) and scattering processes (Botta et al, 2010;Johnson et al, 2016) that take place during melting, the computed melting layer attenuation values are expected to be uncertain. For example, two widely used studies (Haynes et al, 2009;Matrosov, 2008) differ in the computed W-band attenuation values.…”
Section: Introductionmentioning
confidence: 99%